2003
DOI: 10.3989/scimar.2003.67n143
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of <i>Solea solea</i> (Linnaeus, 1758) and <i>Solea senegalensis</i> Kaup, 1858, (Pisces: Pleuronectiformes) from several estuarine systems of the Portuguese coast

Abstract: SUMMARY:The genetic differentiation of Solea solea and Solea senegalensis from several estuarine systems along the Portuguese coast was studied. Nine polymorphic isozyme loci (ACP-1*, ACP-2*, GPI-1*, GPI-2*, sMDH*, ME-1*, ME-2*, MPI* and PGM*) were analysed using starch gel electrophoresis and isoelectric focusing. Differentiation between the species was high (mean average Nei distance of 0.93). The most efficient loci in the diagnosis of the two species were ACP-1*, ME-2* and GPI-2*. S. solea showed a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
2
23
0
4
Order By: Relevance
“…This pattern of low genetic divergence has been reported for other marine fishes (e.g. Gyllensten, 1985;Kinsey et al, 1994;Chikhi et al, 1998;Cabral et al, 2003a, Pinheiro et al, 2005.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This pattern of low genetic divergence has been reported for other marine fishes (e.g. Gyllensten, 1985;Kinsey et al, 1994;Chikhi et al, 1998;Cabral et al, 2003a, Pinheiro et al, 2005.…”
Section: Discussionmentioning
confidence: 76%
“…Here, Castilho and McAndrew (1998) found a significant population sub-structuring for Dicentrarchus labrax (Linnaeus, 1758) juveniles in five estuaries. However, for two species of soles with a similar life history pattern, Solea solea (Linnaeus, 1758) and Solea senegalensis Kaup, 1858, Cabral et al (2003a found a low genetic differentiation. These contradicting results suggest that, although estuaries may contribute to the genetic divergence observed in species occurring in estuarine and open-coast environments (Bilton et .…”
Section: Introductionmentioning
confidence: 99%
“…In common sole, clear signals of geographic differentiation in European waters have been also revealed employing different genetic markers (Kotoulas et al 1995;Exadactylos et al 1998Exadactylos et al , 2003Exadactylos et al , 2007Cabral et al 2003), and even differentiation between cohorts has been found (Guinand et al 2008), suggesting complex patterns of spatial and temporal variation. Absence of large-scale geographical differentiation was found only in one study employing EPIC markers (nuclear exon-primed intron-crossing) .…”
Section: Population Structurementioning
confidence: 96%
“…Despite the commercial importance of sole, population genetic studies in the North-East Atlantic Ocean are relatively scarce, compared to studies in the Mediterranean Sea and the Bay of Biscay (Cabral et al 2003;Garoia et al 2007;Guarniero et al 2002;Guinand et al 2008). Across the NE Atlantic, a pattern of isolation by distance (IBD) was found from the English Channel to the Tunesian Coast with allozyme markers, and the geographic range of signiWcant population structure was estimated at 100 km (Kotoulas et al 1995).…”
Section: Introductionmentioning
confidence: 99%